Optimizing (s, S) policies for multi-period inventory models with demand distribution uncertainty: Robust dynamic programming approaches - QIU, Ruozhen (Institutional Knowledge at Singapore Management University, 2017)
We consider a finite-horizon single-product periodic-review inventory managementproblem with demand distribution uncertainty. We formulate the problemas a dynamic program and prove the existence of an optimal (s, S) policy. Thecorresponding dynamic robust counterpart models are then developed for thebox and the ellipsoid uncertainty sets. These counterpart models are transformedinto tractable linear and second-order cone programs, respectively. Weillustrate the effectiveness and practicality of the proposed robust optimizationapproaches through a numerical study.